(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
In the realm of language and interaction, sentences serve as fundamental units of expression, conveying meaning and enabling communication among individuals. A key aspect of sentences is their communicative function, which varies based on their structure, purpose, and context. This article delves into the various types of sentences used in communication, exploring their characteristics, usage, and impact on effective communication. Whether declarative, imperative, interrogative, or exclamatory, each type of sentence plays a distinct role in shaping conversations, conveying emotions, and eliciting responses. A profound understanding of these sentence types is essential for enhancing communication skills, fostering clearer exchanges, and strengthening interpersonal relationships.